Monte carlo simulation and validation of 6 MV photon beam in various field - Illias, Nur Asiyah (2020)
This study was carried out to simulate and validate 6 MV photon beam on Elekta Synergy LINAC by using EGSnrc Monte Carlo code for various field sizes. Elekta Synergy treatment head model was established using BEAMnrc/EGSnrc Monte Carlo code. The simulation was conducted in four different field sizes, 3 x 3 cm2, 5 x 5 cm2, 7 x 7 cm2 and 10 x 10 cm2. Calculations of depth dose of 6 MV photon beam of four field sizes were performed by using DOSXYZnrc/EGSnrc. The depth dose results obtained from this simulation works were validated by comparing the central axis dose with the ionisation chamber (IC) measurement in a 3D water phantom for the standard field size of 10 cm x 10 cm at SSD 100 cm with less than 2.48% at depth 1.5 cm, 5 cm and 10 cm. The scatter plot of the field size 10 cm x 10 cm is clearly seen and the opening of the jaw is 5 cm for each side from the origin and validated the MLC configuration in the BEAMnrc. The MC model outcome shows that the model is well built and is appropriate design to be use for the dose calculation. The result demonstrated that the Monte Carlo calculation provide a good agreement for the depths beyond depth of maximum dose,dmax = 1.5 cm between the Monte Carlo calculation and IC measurement data for the large field sizes (7 cm x 7 cm and 10 cm x 10 cm) with the percentage difference for the depths 1.5 cm, 5 cm and 10 cm are within ± 2% difference. However, the result shows not a good agreement for the small field sizes (3 cm x 3 cm and 5 cm x 5 cm) were due to loss of the electronic equilibrium, partial occlusion and volume averaging in the small field (6.31% and 9.8% respectively). In conclusion, the EGSnrc Monte Carlo model for the Elekta Synergy LINAC was validated and requires more works on small field radiotherapy.